A case study of a body weight management of an elite gymnast during the preparation period for the 2012 Olympic Games - Chen, H.; Liu, S.; Wang, M.; Huang, Y.; Cui, S.; Zhou, W. (Science of Gymnastics Journal, 2013)
On the very first Science of Gymnastics Journal® in 2009, the authors have reported a successful weight-loss program in China National Gymnastics Team for preparing for 2008 Olympic Game, ever for an elite female gymnastic athlete (Chen, H., 2009).